Green synthesis and application of graphene oxide extracted from Punica granatum. (2023) - Priyadharshini, K.; Rathinavel, S.; Velumani, E.; Manikandan, A.
Abstract: In this work, the green reductant is used for the synthesis of reduced graphene oxide (rGO) from the Punica granatum (pomegranate) extract. The suitability of pomegranate juice was used as a capping agent and also a reductant to form Graphene oxide (GO). The simple modified hummer's method is used to oxidize the graphite for the synthesis of graphene oxide. The graphene oxide has been prepared by the oxidation of graphite with H2 SO4 . Finally, rGO synthesized from the extract of Punica granatum and the contemplating sorption was good for removing the methylene blue (MB). The sorption method is well-suitable for the new adsorbent with pseudo-second-order kinetics and Langmuir isotherm models. Synthesized rGO samples exhibited excellent activity as an adsorbent for the removal of dye. X-ray powder diffraction (XRD) and Fourier Transform Infrared spectroscopy (FTIR) confirmed the formation of graphene. The study of the morphological structures was carried out by Field emission scanning electron microscopy (FESEM). The used technique is eco-friendly, low-cost, and capable of the large-scale production of rGO.